The Development of Problem-Based Learning Management Activities to Promote Attitude Towards Science and Technology Subjects of Grade 5 Students - Apitchaya Thomjaroen; Wisarut Payoungkiattikun; Tipubon Tippalert (Gagasan Pendidikan Indonesia, 2023)
The objectives of this research were; (1) to develop a problem-based learning management activity that is effective according to the 80/80 criterion and (2) to promote attitudes towards learning science and technology subjects to pass the 70% threshold. This research is a developmental research model which focuses on design and innovation development and is divided into 2 phases: the development process and the assessment process. This research is in phase 2. The sample group consisted of 32 grade 5 students studying in the first semester of the academic year 2022 at a school in Kalasin Province. Research tools include; (1) 4 learning management plans and (2) attitudes toward learning science and technology subject tests. The statistics used in data analysis were percentage, mean, and standard deviation. Collect data on attitudes toward learning science and technology subjects with a 5-level rating scale and 10-item list. The results showed that; (1) The overall efficiency of the problem-based learning management activities was at the highest level. (X = 4.99, S.D. = 0.02). Moreover, (2) The effect of students' learning attitude towards science and technology after organizing the problem-based learning management activities was high (X = 4.38, S.D. = 0.84).